ECO ENZYME ANTIBACTERIAL ACTIVITY TEST AGAINST ESCHERICHIA COLI BACTERIA ISOLATED FROM DOG SKIN - Gayanti, Alya Nita Shena; Suartha, I Nyoman; Sudipa, Putu Henrywaesa (Buletin Veteriner Udayana, 2023)
Ecoenzyme liquid has benefits as a natural disinfectant. This study aimed to determine the antibacterial activity of ecoenzyme fluid made from papaya peel ( Carica papaya L. ), soursop skin ( Annona muricata L .), neem leaf ( Azadirachta indica ) and lemongrass ( Cymbopogon winterianus ) against Escherichia coli bacteria isolated from dog skin in vitro . In this study, 4 concentrations of ecoenzymes were used, namely 25%, 50%, 75%, 100%, and 1 positive control (antibiotic Kanamycin) and 1 negative control. In this study, the research data were analyzed for variance and continued with the Games-Howell test. The results showed that the zones of inhibition on ecoenzymes with concentrations of 25%, 50%, 75%, and 100% were 0 ± 0, 0 ± 0, 8.42 ± 0.46, and 8.56 ± 0.96, respectively. positive was 20.95 ± 1.43 and negative control was 0 ± 0. The most effective ecoenzyme liquid inhibiting the growth of Escherichia coli in vitro was a concentration of 100%. It is necessary to do further research, namely the testing of ecoenzyme fluid against E. coli bacteria in vitro.